The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1365-2249.1996.tb08304.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of experimental allergic encephalomyelitis (EAE) by administration of nitric oxide (NO) synthase inhibitors

Abstract: SUMMARYMacrophages constitute a large proportion of the inflammatory cells that infiltrate the central nervous system (CNS) of animals with EAE. Through the production of inflammatory mediators these infiltrating macrophages can contribute to the regulation of the immune reaction within the CNS, that eventually results in neurological deficits associated with EAE. NO, a free radical produced by macrophages and other cell types. has been pul rorward as such an immune mediator.In the present study we show that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…A number of anti-inflammatory pathways are postulated to be important in neuroprotection in the context of neurodegeneration. Specifically, the ROS detoxification pathways are implicated, and a major role for ROS in the pathophysiology of multiple sclerosis has been demonstrated in both pathological and experimental studies [17][18][19][20][21]. ROS include superoxide ions, hydrogen peroxide, nitric oxide and peroxynitrite, all of which are produced as part of the inflammatory response and have a potential role in causing tissue damage in [22], thus limiting the formation of strong neurotoxic oxidants including both the hydroxyl radical and peroxynitrite in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…A number of anti-inflammatory pathways are postulated to be important in neuroprotection in the context of neurodegeneration. Specifically, the ROS detoxification pathways are implicated, and a major role for ROS in the pathophysiology of multiple sclerosis has been demonstrated in both pathological and experimental studies [17][18][19][20][21]. ROS include superoxide ions, hydrogen peroxide, nitric oxide and peroxynitrite, all of which are produced as part of the inflammatory response and have a potential role in causing tissue damage in [22], thus limiting the formation of strong neurotoxic oxidants including both the hydroxyl radical and peroxynitrite in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Data to support various mechanisms for the anti-inflammatory effects of IFN-␥ have been described, and these include antiproliferative and proapoptotic effects that involve NO production by macrophages or resident microglia (53)(54)(55)(56)(57) or the inhibition of the development of IL-17-producing CD4 ϩ cells that are associated with autoimmunity (38 -41). Our immunohistological analyses indicate no major differences in the numbers of apoptotic cells in the mice in the different groups (data not shown), but this may be due to the greater number of infiltrating cells at the peak of disease in the lower Ag dose groups combined with the susceptibility of infiltrating CD4 ϩ cells to undergo apoptosis in the CNS (58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups found that pharmacological inhibitors of iNOS, particularly relatively selective aminoguanidine, potently protect against neurological deficits in EAE models in mice and rats (66,284). However, conflicting data with pharmacological inhibitors of iNOS and the iNOS gene deletion have also been reported (84,132,223). The paradoxical exacerbation of neurological deficits found in these latter studies was explained by the fact that iNOS-derived NO potently suppresses Th1-dependent immune responses, and that inhibition or removal of the enzyme prevents the natural reduction of immune responses (131).…”
Section: Multiple Sclerosismentioning
confidence: 99%